The Impact of Principal’s Leadership and Teacher’s Character on Teacher’s Professional Competence - Hastuti, Sri; Lian, Bukman; Mahasir, Mahasir (Journal of Social Work and Science Education, 2023)
A teacher’s level of professional competence is mostly determined by elements inside of him or her. The effectiveness and efficiency of the principal determine the success of a given institution. The goal of the study was to determine how the principal’s management style and the characteristics of teachers affected the teachers’ professional competency in the SD Negeri Belida Darat district. This study helps all members of the teaching staff by enhancing instructors’ professional competence. The goal of this study was to identify and characterize the relationship between the professional competence of public elementary school teachers in the Belida Darat sub-district, Muara Enim district, and the principal’s leadership and teacher character. The approach taken is called the survey technique, and it explains how the independent variables principal leadership (X1) and teacher character (X2)-have an impact on the dependent variable, or the teacher’s professional competence (Y). Quantitative analysis will be used to analyze and analyze all of the data gathered. All of the instructors and administrators of the public elementary schools in Belida Darat District, Muara Enim Regency, make up the population. Each school is used in the research sample. The leadership of the principal has a substantial impact on teachers’ professional competence, as shown by the significant value of 0.000, which is smaller than the probability of 0.05, and the t count of 7.715, which is higher than the t table of 1.9886. The value of the relationship between a teacher’s character and professional skill is substantial.